Cost-effectiveness of combining systematic identification and treatment of co-morbid major depression for people with chronic diseases: the example of cancer. Issue 7 (May 2014) - Walker, S.; Walker, J.; Richardson, G.; Palmer, S.; Wu, Q.; Gilbody, S.; Martin, P.; Hansen, C. Holm; Sawhney, A.; Murray, G.; Sculpher, M.; Sharpe, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Co-morbid major depression occurs in approximately 10% of people suffering from a chronic medical condition such as cancer. Systematic integrated management that includes both identification and treatment has been advocated. However, we lack information on the cost-effectiveness of this combined approach, as published evaluations have focused solely on the systematic (collaborative care) treatment stage. We therefore aimed to use the best available evidence to estimate the cost-effectiveness of systematic integrated management (both identification and treatment) compared with usual practice, for patients attending specialist cancer clinics. Method We conducted a cost-effectiveness analysis using a decision analytic model structured to reflect both the identification and treatment processes. Evidence was taken from reviews of relevant clinical trials and from observational studies, together with data from a large depression screening service. Sensitivity and scenario analyses were undertaken to determine the effects of variations in depression incidence rates, time horizons and patient characteristics. Results Systematic integrated depression management generated more costs than usual practice, but also more quality-adjusted life years (QALYs). The incremental cost-effectiveness ratio (ICER) was £11 765 per QALY. This finding was robust to tests of uncertainty and variation in key model parameters. Conclusions Systematic integrated management of co-morbid major depression in cancer patients is likely to be cost-effective at widely accepted threshold values and may be a better way of generating QALYs for cancer patients than some existing medical and surgical treatments. It could usefully be applied to other chronic medical conditions.